Using Spotify as a Learning Medium in Developing Students' Listening Comprehension - Frensiska, Nadila; Jamiluddin; Mashuri; Muhammad Arid (Institut Agama Islam Negeri Palopo, 2024)
This study aimed to prove whether or not the use of Spotify can develop the listening comprehension of the tenth-grade students of SMA Negeri 2 Palu. The research design used in this study was a quasi-experimental design, and used a quantitative approach to analyze the data. The population of this study was the tenth-grade students of SMA Negeri 2 Palu. The researcher used purposive sampling and chose two groups: XD as the experimental group and XE as the control group, which each group consisted of 32 students. The instrument in collecting data was test (pre-test and post-test). The results of this study show that there is a significant difference in the increase in students' listening after being taught through the Spotify application. Data analysis shows that the tcounted (7,216) is higher than ttable (1,670) by applying a significance level of 0.05 with degrees of freedom (df) = 62. This means that the hypothesis is accepted. So, it can be said that Spotify can develop the students’ listening comprehension in learning English at SMA Negeri 2 Palu.